Avaliação dos aspectos técnicos e econômicos entre estruturas pré-fabricadas e moldadas in loco - Pagoto, Marcos Vinícius (2013)
Some alternatives are emerging to industrialize construction. Precast elements are an option, combining speed of execution, strict quality control and high organizational level of production. In this work, we carried out a comparison of execution costs between precast structures and molded on the spot for a residence of 2 floors. To obtain the results, the methodology used was market research, requesting budgets of companies specializing in the area of both structures as precast structures molded on the spot. Making a budget average cost of both construction processes, we have reached a value 4% more expensive for the precast structure. The precast, even though more expensive, it was considered advantageous for the study case. The economic advantage can not be restricted only to the gross cost of construction should take into consideration the time of execution, quality control and reliability of materials and construction process, optimization of the work, which generate savings in construction site, with hand labor and decrease waste.